Global Awareness Dialogue Project: Exploring Potential for Faculty Transformation Through a Professional Development Series. (October 2019) - Senyshyn, Roxanna M.; Smith, Paula
This article examines a faculty professional development program aimed at engaging faculty in an ongoing discussion about global awareness and the practices surrounding teaching and learning in a linguistically and culturally diverse classroom. The program is modeled on two key components: the engagement of undergraduate students and faculty in a structured dialogue outside the classroom and the contributions of experts to faculty discussions to locate and contextualize best practices. The initiative's potential to affect faculty perspectives is explored through a transformative learning framework. Short-term and long-term assessments show that participants were motivated to improve and implement new instructional practices.